STRATEGI PENGEMBANGAN DESA BELUMBANG MENUJU DESA WISATA BERBASIS MASYARAKAT DI KABUPATEN TABANAN, BALI - Anggaryani, Ayuning; Anom, I Putu; Narottama, Nararya (Jurnal Master Pariwisata (JUMPA); Volume 09, Nomor 02, Januari 2023DO - 10.24843/JUMPA.2023.v09.i02.p06, 2023)
Belumbang Village is located in Kerambitan District, Tabanan Regency, Bali. The potential of the village of yet to go to a tourism village is natural potential, cultural potential, fitness activities, spiritual and artificial attractions. However, only a few have been actively implemented, therefore it is necessary to formulate a development strategy that can be applied in Belumbang Village so that in the future it can become a sustainable and community-based tourism village. Then the specific objectives are to identify the existence of potential tourist attractions owned by Belumbang Village, to identify and analyze internal and external factors in developing Belumbang Village and to formulate strategies in developing Belumbang Village towards a communitybased Tourism Village. This study used descriptive qualitative method. With the data collection technique is done by observation, interviews, document studies and FGD. Data were analyzed by SWOT, IFE and EFE analysis and QSPM. Based on the results of the SWOT analysis, there are 11 alternative strategies that can be applied in Belumbang Village. Then, based on the results of the QSPM analysis, there are 2 alternative strategies that are prioritized, namely maximizing the potential for wellness tourism that is developing in Bali and making more attractive tour packages by utilizing existing potential. It can be concluded that contributions from various parties such as the government, stakeholders and local communities are needed in developing a strategy for developing Belumbang village to be a community-based tourism village. Keywords: development strategy; tourist village; SWOT analysis.